2022
DOI: 10.1186/s13073-021-01008-4
|View full text |Cite
|
Sign up to set email alerts
|

T cell receptor beta germline variability is revealed by inference from repertoire data

Abstract: Background T and B cell receptor (TCR, BCR) repertoires constitute the foundation of adaptive immunity. Adaptive immune receptor repertoire sequencing (AIRR-seq) is a common approach to study immune system dynamics. Understanding the genetic factors influencing the composition and dynamics of these repertoires is of major scientific and clinical importance. The chromosomal loci encoding for the variable regions of TCRs and BCRs are challenging to decipher due to repetitive elements and undocume… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 87 publications
4
25
0
Order By: Relevance
“…The fact that we identified 79 undocumented (non-IMGT) alleles in only 9 unrelated individuals highlights the severe deficits that currently exist in germline databases. Considering our findings alongside other recent efforts underlines the work that remains to be done to fully catalog TR gene diversity in the human population (9,26). At present, the impact that these missing germline genes and alleles has on the analysis and interpretation of TCR repertoire sequencing studies is not clear, but would be expected to have profound effects on germline gene/allele assignment efforts, similar to what has been noted for IG repertoires.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The fact that we identified 79 undocumented (non-IMGT) alleles in only 9 unrelated individuals highlights the severe deficits that currently exist in germline databases. Considering our findings alongside other recent efforts underlines the work that remains to be done to fully catalog TR gene diversity in the human population (9,26). At present, the impact that these missing germline genes and alleles has on the analysis and interpretation of TCR repertoire sequencing studies is not clear, but would be expected to have profound effects on germline gene/allele assignment efforts, similar to what has been noted for IG repertoires.…”
Section: Discussionsupporting
confidence: 73%
“…A critical step in analyzing TCR repertoire sequencing data is the alignment of reads to a TCR germline gene database in order to identify the V, D and J allele present in a given read. Therefore, it is important to utilize a complete and accurate allele database (9). To determine the extent to which targeted long-read capture sequencing can help complete TCR germline databases, we first genotyped the alleles in both trios to measure the genotyping accuracy and then genotyped the remaining samples (Figure 5; Supplementary Table 1).…”
Section: Detection Of Tra/d and Trb Allelesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has suggested that polymorphisms within the immunoglobulin V-gene region are not completely captured by existing SNP array technology, and have been underrepresented in previous genome-wide association studies ( Watson and Breden, 2012 ). SNP coverage of the TCRβ locus is thought to be even sparser ( Omer et al, 2022 ), and thus, much of the actual TCRβ variation present within our data cohort is likely not captured by the SNP dataset used here (which contains 7,304 SNPs within the TRB locus, hg19:chr7:141950000–142550000). Lastly, we have used the recombination statistics from non-productive rearrangements here as a means of studying the V(D)J recombination generation process in the absence of selection; however, we acknowledge that the repertoire of non-productive rearrangements may be an imperfect proxy for a pre-selection TCR repertoire.…”
Section: Discussionmentioning
confidence: 99%
“…The TCRA and TCRB regions have been historically difficult to reliably map using short read sequencing due to their repetitive and complex nature. While recent work has identified many new TRBV alleles, many more undocumented TRBV alleles likely remain to be discovered ( Omer et al, 2022 ). As such, the incomplete characterization of the TCRB locus limited our ability to infer the correct V(D)J -gene allele for each final nucleotide sequence.…”
Section: Discussionmentioning
confidence: 99%